2015
DOI: 10.3109/09638288.2015.1059495
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a home-based program to improve handwriting after stroke: a pilot study

Abstract: facilities, health-related websites and in a seniors' newspaper. Eligibility criteria included having sustained a stroke at least three months previously, having self-reported difficulties with, and goals related to, handwriting, being able to hold a pen, and having sufficient cognitive and communication skills to complete a daily home program.A four-week, home-based handwriting training program was delivered by an occupational therapist. The intervention applied principles of task-specific motor training, inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 122 publications
(353 reference statements)
1
3
0
Order By: Relevance
“…Ten musculoskeletal physiotherapists were recruited from two musculoskeletal outpatient clinics in one NHS trust. This number is comparable to that in the study by Simpson, McCluskey, Lannin, and Cordier (), who also explored the acceptability of an intervention. There were two male and eight female physiotherapists in the present study, with a mean of 10.6 years of clinical experience.…”
Section: Resultssupporting
confidence: 73%
“…Ten musculoskeletal physiotherapists were recruited from two musculoskeletal outpatient clinics in one NHS trust. This number is comparable to that in the study by Simpson, McCluskey, Lannin, and Cordier (), who also explored the acceptability of an intervention. There were two male and eight female physiotherapists in the present study, with a mean of 10.6 years of clinical experience.…”
Section: Resultssupporting
confidence: 73%
“…Fourteen of the twenty people enrolled in the program completed the full program which equals a 70% successful participation rate. Other feasibility studies [42,43] with chronic stroke patients reported similar participation numbers after testing home-based or tele-physiotherapy programs. Our IG had a high exercise self-efficacy.…”
Section: Feasibilitymentioning
confidence: 80%
“…This is because handwriting requires complex coordination of the muscles of the upper extremities 3 . If writing is not possible with the dominant hand, patients with hemiplegia who have a paralyzed dominant hand have to write and draw with their nondominant hand 4,5 .…”
Section: Introductionmentioning
confidence: 99%